Analisis Pertanggungjawaban Hukum Tukang Gigi dan Perlindungan terhadap Konsumen Jasa Tukang Gigi di Indonesia - Sedyaningtyas, Sekar; Lubis, Arief Fahmi; Rokhmat, Rokhmat (Syntax Corporation, 2025)
The work of dentists has been regulated in the Regulation of the Minister of Health Number 39 of 2014 concerning Coaching, Supervision and Licensing, Dentist Work. The authority of the dentist only makes and installs removable dentures, either partially or fully, using heat curing acrylic material and meets the health element where it does not cover the remaining tooth roots. Although the standard of work and authority of dentists has been regulated, many dentists ignore it by doing work outside of their authority and often do not meet medical rules in practice. This can certainly cause losses for consumers, both material and immaterial losses. There must be a balance between the accountability carried out by dentists and legal protection for consumers of dentist services who feel disadvantaged so that consumers are not always in a weak position. The research conducted is normative juridical and carried out with several approaches such as legislation, conceptual and case study approaches. Primary, secondary and tertiary data are used to answer the problems of this study. The results of this study show that the accountability of dentists can be carried out in the form of administrative law, civil law and criminal law. Consumer protection has been regulated in Law Number 8 of 1999. Dentist consumer protection is carried out by providing compensation. In addition, it can also be done by holding coaching and supervision carried out by the government.